Validation of Antidiabetic Potential of Gymnocarpos decandrus Forssk. Issue 24 (17th December 2021) - El-Hawary, Seham S.; Mubarek, Mahmoud M.; Lotfy, Rehab A.; Hassan, Ahmed R.; Sobeh, Mansour; Okba, Mona M.
Abstract: Gymnocarpos decandrus Forssk. is a well-known grazing wild plant. This study targets scientific validation of its claimed antidiabetic activity and exploring its bioactive metabolites. Chromatographic purification of G. decandrus ethanol extract (GDEE) allowed isolation of vitexin (C1), protocatechuic acid (C2) and quercetin (C3) . HPLC-PDA-MS/MS enabled identification of nineteen metabolites; 13 flavonoids, 5 saponins, and 1 phenolic acid in G. decandrus and four in the genus Gymnocarpos for the first time. The antidiabetic potential was evaluated via testing the Coxsackie B4 virus and α -glucosidase inhibitory potentials. C3 exhibited its potent antiviral activity through blocking of the virus attachment (96.28%, SI 4.41) and virus inactivation before adsorption (91.47%, SI 4.78). GDEE and C1–C3 showed dose dependent α -glucosidase inhibitory activity with IC50 of 733.9, 293.3, 118.1 and 69.1 µg/mL, respectively. Our study represents the sole complete map for G. decandrus secondary metabolites and presents it as promising drug for diabetes management. GRAPHICAL ABSTRACT: UF0001